2005
DOI: 10.1159/000084018
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Intraperitoneal Chemotherapy for Patients with Scirrhous Gastric Cancer

Abstract: Background: The prognosis for patients with scirrhous gastric cancer (SGC) is extremely poor. To improve the patients’ prognosis, laparoscopic-assisted intraperitoneal chemotherapy (IPC) was introduced for SGC. In this study, we analyzed whether IPC reduced the number of cancer cells in the peritoneal cavity of patients or changed the gene expression levels of cytokines in the peritoneal cavity. We also investigated whether IPC improved the prognosis of patients with SGC. Methods: Total RNA was extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…LSGC, localized type IV scirrhous gastric cancer; LP, linitis plastica; OGC, other types of advanced gastric cancer. and strong chemotherapy, including S-1, may be a more favorable option than aggressive surgery or palliative gastrectomy (2,3,13,16). In the present study, peritoneal cytology was an independent prognostic factor in SGC.…”
Section: A B C Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…LSGC, localized type IV scirrhous gastric cancer; LP, linitis plastica; OGC, other types of advanced gastric cancer. and strong chemotherapy, including S-1, may be a more favorable option than aggressive surgery or palliative gastrectomy (2,3,13,16). In the present study, peritoneal cytology was an independent prognostic factor in SGC.…”
Section: A B C Discussionsupporting
confidence: 48%
“…SGC has been shown to possess unique clinicopathological characteristics and a poor survival outcome despite curative gastrectomy (10)(11)(12)(13)(14)(15)(16)(20)(21)(22)(23). One reason for the poor prognosis specific to SGC is the difficulty in early detection.…”
Section: A B C Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal metastasis is a predominant metastatic pattern in advanced gastric cancer [1,2] , and the prognosis of patients with peritoneal metastasis of gastric cancer is poor [3] . The median survival time (MST) of such patients is reported to be 3-6 months [4] , and a standard regimen against peritoneal metastasis of gastric cancer has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the treatment recommendations for gastric cancer in the event of positive cytology range from palliative chemotherapy to attempts at neo-adjuvant therapies followed by surgical resection. However, the results of published randomized clinical trials of adjuvant perioperative intra-peritoneal chemotherapy have not fully demonstrated any significant improvement in survival as compared with surgery alone, especially in the cases with P+ (Cunliffe & Sugarbaker, 1989;Cheong et al, 2007;Hagiwara et al, 1992;Ikeguchi et al, 2005;Kunisaki et al, 2002;Sauter et al, 1994). Therefore, a reliable and appropriate standard prophylactic regimen for peritoneal recurrence in patients with gastric cancer needs be established.…”
Section: Introductionmentioning
confidence: 99%